Seed Quality of Paddy Variety (Oryza sativa L.) Resistant to Vegetative Phase Drought Stress - Winggi Anggun Jati; Zaidan Panji Negara; Firdaus Sulaiman (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
Drought is an abiotic stress that can affect paddy yields by inhibiting growth, thereby reducing the quality of the seeds produced. This study aimed to find out the best seed quality of several paddy varieties produced from the plants experiencing drought stress in the vegetative phase. The varieties used in the study were Inpago 12, Unsoed 1, Inpago 4, Inpago 5, Inpago 9, Inpago 8, Inpago 10, Inpara 8, Inpara 9, Rindang 1, Rindang 2, Situ Patenggang, Towuti, and Batu Tegi. The drought stress was applied to the vegetative phase of the plant by reducing the intensity of water supply (63.5% moisture content), then the resulting seeds were tested in the laboratory. The results of the study showed that the highest seed quality value in the drought stress treatment of the vegetative phase were the Inpara 8 variety, followed by the Towuti variety with 93.33% and 88% germination values, 82.67% and 70% simultaneous growth, 12.11% and 8.44% germination rate, 64% and 64% germination strength, and 18.99 and 16.83 vigor indexes. Meanwhile, the lowest seed quality was the Inpago 8 variety with 26% germination value, 21.33% simultaneous growth, 1.33% germination speed, 3.33% germination strength, and 2.71 vigor index. Among all the varieties tested, the Inpara 8 and Towuti are those with the best seed quality values ​​after experiencing drought stress during the vegetative phase.